Development and Validation of a Predictive Scale for Stroke and Cognitive Impairment in Atherothrombotic Carotid Disease - Sardorbek Yuldashev (International Scientific and Current Research Conferences, 2025)
Atherothrombotic lesions of the internal carotid arteries are among the leading causes of ischemic stroke and cognitive decline. Traditional assessment focused primarily on the degree of stenosis fails to reflect the complex interplay between vascular, metabolic, and neurocognitive factors that determine clinical outcomes. This study was aimed at developing and validating a predictive scale that integrates structural, functional, biochemical, and cognitive parameters to improve individual risk assessment and optimize preventive strategies. A prospective cohort of 357 patients with atherothrombotic extracranial arterial disease was examined. Independent predictors of ischemic stroke and cognitive decline were identified using multivariate Cox regression analysis adjusted for age, sex, hypertension, diabetes, and smoking. The evaluated factors included bilateral or combined internal carotid and vertebral artery stenosis, cerebrovascular reserve (CVR), plaque morphology, high-sensitivity C-reactive protein (hs-CRP), and Montreal Cognitive Assessment (MoCA) score. The discriminative performance of the models was analyzed using receiver operating characteristic (ROC) curves, and a Predictive Risk Scale (PRS) was derived based on Cox regression coefficients and validated during 12 months of clinical follow-up. The analysis revealed that combined internal carotid and vertebral artery stenosis (HR 1.93, p<0.001), decreased CVR below 30% (HR 1.65, p=0.003), and unstable plaques (HR 1.48, p=0.006) were the strongest predictors of ischemic stroke. For cognitive impairment, MoCA score below 24 (HR 1.67, p=0.004) and age above 70 years (HR 1.34, p=0.039) were significant independent factors. The integrated PRS demonstrated an area under the ROC curve of 0.88 (95% CI 0.84–0.92), with sensitivity of 84% and specificity of 81%. The use of the PRS with individualized prevention reduced the incidence of cerebrovascular events from 23.3% to 6.7% within 12 months of observation. Economic efficiency analysis indicated that implementation of the scale decreased direct treatment costs by approximately 65% per patient, largely through reduced rates of stroke-related disability and hospitalization. The developed Predictive Risk Scale incorporates anatomical (stenosis and plaque morphology), functional (cerebrovascular reserve), biochemical (hs-CRP), and cognitive (MoCA) variables, providing a comprehensive approach to evaluating stroke and cognitive decline risk. Integration of this scale into clinical practice enables physicians to identify high-risk individuals, personalize preventive measures, and rationally allocate medical resources. The findings demonstrate that a multifactorial model significantly surpasses traditional stenosis-based assessment, facilitating more accurate prognosis, reduced stroke incidence, preserved cognitive health, and improved cost-effectiveness. The proposed scale may serve as a valuable tool for both primary and secondary prevention of cerebrovascular and cognitive complications in patients with atherothrombotic carotid disease.